Between Memory and Dialogue History. Air War in Modern German-English Discourse - Łukasik, Przemysław (Sensus Historiae, 2020)
As a concept of dialogical history we understand the process of creating transnational memory in the course of complementing individual national memories. In the opinion of the German memoryologist Aleida Assmann, the creator of the concept, dialogue history is particularly important for nations with a difficult past. A responsible and empathic telling of a shared story can be the foundation of a normal relationship in the future. The purpose of the article is to analyze the phenomenon of dialogue history on the example of the English-German debate on air war. At the beginning of the 21st century, we observed in Germany a renaissance of memories related to the history of the destruction of German cities during World War II. Books written by Sebald and Friedrich initiated a wave of publications on the subject of German victims of Allied bombing. Those undertakings whichaimed at depicting Germans as victims of the War and the language used for the description (equating the bombing of German cities with the Holocaust) caused vivid reactions, especially in countries that conducted air operations over the Third Reich, i.e. the USA and the UK. The answer were newly emerging British publications which were polemic and referred both to the facts related to the air war and to the accompanying assessments (comparing Churchill to Hitler). The effect of this debate is the emergence of the Anglo-German history of air dialogue.